Developing Digital Competence and Social Inclusion for Madrasah Teachers in Malang Regency - Muhammad Faishal Aminuddin; Romel Masykuri; Sigit Prawoto; Torik Abdul Aziz Wibowo; Yusril Adyan (Sahwahita: Community Engagement Journal, 2026)
Quality education is a crucial foundation for realizing a prosperous and competitive society, as outlined in the Sustainable Development Goals (SDGs), particularly Goal 4: Quality Education. In Malang Regency, Islamic schools (madrasah) play a significant role in providing education to the community, with the number of elementary, junior high, and senior high schools (Madrasah Ibtidaiyah, Tsanawiyah, and Aliyah) continuing to increase. However, the main challenges faced are teachers limited digital technology skills and a lack of understanding of the importance of social inclusion in education. This community service program aims to improve digital competency and social inclusion among madrasah teachers in Malang Regency. Planned activities include training on the use of digital technology for learning, including the use of digital platforms such as Google Classroom, and increased understanding of the importance of social inclusion in education. This program is expected to help madrasah teachers adopt digital technology and create a more inclusive and equitable educational environment. Partners face several challenges, such as limited digital access and skills, a lack of understanding of social inclusion, and a lack of ongoing training for teachers. Through this training, it is hoped that teachers will be able to utilize technology for more creative and effective learning and apply the principles of inclusivity in the teaching process. This program will support the transformation of madrasa education in Malang Regency towards more adaptive, inclusive, and sustainable education